ChemInform Abstract: Chelation‐Assisted Rh(III)‐Catalyzed C2‐Selective Oxidative C—H/C—H Cross‐Coupling of Indoles/Pyrroles with Heteroarenes. Issue 41 (19th September 2013) - Qin, Xurong; Liu, Hu; Qin, Dekun; Wu, Qian; You, Jingsong; Zhao, Dongbing; Guo, Qiang; Huang, Xiaolei; Lan, Jingbo
Abstract This is the first example of a catalytic system promoting an oxidative C—H/C—H heterocoupling not only between electron‐rich heteroarenes but also between electron‐deficient and electron‐rich ones.